Roles of differently polarized macrophages in the initiation and progressionof pancreatic cancer - Storz, Peter (Frontiers in Immunology, 2023)
During development of pancreatic cancer macrophage-mediated inflammatory processes and the formation of cancerous lesions are tightly connected. Based on insight from mouse models we provide an overview on the functions of classically-activated pro-inflammatory and alternatively-activated anti-inflammatory macrophages in the initiation and progression of pancreatic cancer. We highlight their roles in earliest events of tumor initiation such as acinar-to-ductal metaplasia (ADM), organization of the fibrotic lesion microenvironment, and growth of low-grade (LG) lesions. We then discuss their roles as tumor-associated macrophages (TAM) in progression to high-grade (HG) lesions with a cancerous invasive phenotype and an immunosuppressive microenvironment. Another focus is on how targeting these macrophage populations can affect immunosuppression, fibrosis and responses to chemotherapy, and eventually how this knowledge could be used for novel therapy approaches for patients with pancreatic ductal adenocarcinoma (PDA).